Analysis of Bank Health Level Using the RGEC Method at BCA Syariah (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
In carrying out its duties as an intermediary institution, banks must be careful and pay attention to the risk aspects that can result from operational activities of fund management, because banks manage deposits of funds from the public. Therefore, banks are obliged to maintain and maintain the mandate of the community by managing funds carefully and paying attention to risk management which can affect the level of bank health. The purpose of this study is to determine the health level of BCA Syariah Bank from 2017 to 2021 based on the RGEC method which includes four components, namely Risk Profile (Risk Profile), GCG (Good Corporate Governance), Earning (Rentability), and Capital (Capital). This research method uses quantitative research methods with a descriptive approach. The type of data used in this study is secondary data obtained from the financial statements of BCA Syariah Bank for five consecutive years from 2017 to 2021. The results of this study indicate that the health level of Bank BCA Syariah from 2017 to 2021 as measured using the RGEC method through eight indicators (NPF, FDR, PDN, ROA, ROE, NI, BOPO, and CAR) received a Very Healthy predicate.